Notice of Public Scoping Meeting - U.S. Coast Guard::::::; U.S. Maritime Administration::::::; California State Lands Commission:::::: (U.S. Coast Guard)
Public meeting in which Lupe Anguiano serves as a testimony to the endangerment of marine life if LNG is implemented. Attaches 7 pieces of evidence to reject LNG project.